On the concept, taxonomy, and transculturality of disordered grief - Gouveia, Afonso (Frontiers in Psychology, 2024)
The enduring question of whether grief can ever be pathological (and, if so, when) has been shrouding mental health and psychiatric care in the last years. While this discussion extends beyond the confines of psychiatry to encompass contributions from diverse disciplines such as Anthropology, Sociology, and Philosophy, scrutiny has been mainly directed towards psychiatry for its purported inclination to pathologize grief-an unavoidable facet of the human experience. This critique has gained particular salience considering the formal inclusion of Prolonged Grief Disorder in the 11th edition of the International Classification of Diseases (ICD-11) and the subsequent Text Revision 5th Edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5-TR). This paper contends that the inclusion of Prolonged Grief Disorder as a diagnostic entity may be excessively rooted in Western cultural perspectives and empirical data, neglecting the nuanced variations in the expression and interpretation of grief across different cultural contexts. The formalization of this disorder not only raises questions about its universality and validity, but also poses challenges to transcultural psychiatry, due to poor representation in empirical research and increased risk of misdiagnosis. Additionally, it exacerbates the ongoing concerns related to normativism and lack of genuine cultural relativism within the DSM. Furthermore, the passionate discussion surrounding the existence, or not, of disordered forms of grief may actually impede effective care for individuals genuinely grappling with pathological forms of grief. In light of these considerations, this paper proposes that Prolonged Grief Disorder should be approached as a diagnostic category with potential Western cultural bias until comprehensive crosscultural studies, conducted in diverse settings, can either substantiate or refute its broader applicability. This recalibration is imperative for advancing a more inclusive and culturally sensitive understanding of grief within the field of psychiatry.